Komposisi Vegetasi Mangrove di Muara Sungai Siganoi Sorong Selatan - Papua - Yohanes Y. Rahawarin (Universitas Atma Jaya Yogyakarta, 2005)
The research was aimed to figure out the structure and composition of mangrove species in the delta of Siganoi River, Inanwatan District, South Sorong Regency, Papua. Belt transect was used and the data was analyzed using formula according to Clintron and Novelly. Research showed that ten species (seven genus) from five families were found in this area. At tree and sapling stages, Sonneratia alba performed the highest density with 324,1 trees/ha and 765,5 sapling/ha respectively, while at seedling stage Aegiceras corniculatumc with 69 seedling/ha. The highest frequency was found on trees and sapling of Sonneratia alba 0,966 and 0,431 respectevely. At the seedling stage, the highest frequency was found on species Aegiceras corniculatum (3970).